Analisis Yuridis Tindak Pidana Perpajakan Yang Dilakukan Secara Berlanjut (Analisa Putusan Nomor 292/Pid.Sus/2020/PN JKT.SEL) - Tofiq, Tri Agung; Riyadi, Slamet (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
Tax crimes must indeed be tightened, the number of criminal violations makes state revenue much reduced. So that this has a very detrimental impact on state finances, so it is necessary to have firmness on these criminal acts that must be handled properly so as not to harm the community and the state. The issues discussed in this thesis are How is the basis for the judge's consideration in deciding tax crime cases in decision Number 292 / Pid.Sus / 2020 / Pn Jkt.Sel. As well as how the Judge applies the principle correctly in deciding crimes in tax crime cases decision Number 292 / Pid.Sus / 2020 / Pn Jkt.Sel. The research method used is normative juridical research using literature data from various literature, books, journals, laws and regulations, etc. Data analysis is carried out in a qualitative normative way. The results showed that the application of criminal law in decision number 292/Pid.Sus/2020/Pn Jkt.Sel had fulfilled the material law in the provisions of Article 64 paragraph (1) of the Criminal Code. Also, the Judge's consideration in applying crime in taxation considers several elements, as follows; (1) Everyone; (2) Representatives, attorneys, employees of Taxpayers, or other parties who order to do (3) Intentionally misuse or use without rights the Taxpayer Identification Number (NPWP) or Taxable Entrepreneur Confirmation that can cause state losses; (4) Several acts, though each an offence or offence, are related in such a way that it must be regarded as one continuing act.